PENGUKURAN KAPASITAS SIMPAN RELATIF BERBAGAI TIPE SIMCARD MENGGUNAKAN CITRA RADIOGRAFI - MAIYENA, SRI (IAIN Batusangkar, 2012)
This research was aimed at finding out the usage of radiological physics, i.e. the use of radiology in projecting the image of a constituent material without damaging the outer profile, calibrating radiological picture with aluminum profiles and measuring the relative sim card storage capacity of hand phones. The test was conducted to five types of sim cards along with a ladder-shaped aluminum profile. Photography radiology was performed energy 50 kv. Then the analysis of image quality was done by using software of new image analyzer 2007. Image calibration process was done by using the results of aluminum profile image. The results of the photographic image were recorded 20 times, and then selected the best image. Then the image result obtained was used to calibrate the thickness of aluminum profile. From the calibration it was found the function equationof the grayscale, y=143,9e-0,18x with the correlation 0,974. As the result of the calibration, it was obtained the relative thickness of sim cards toward aluminum; between 0,3877 ? 0,7423mm. The density measurement of the sim card with grayscale was ranging between 125-134. The density shows the relative simcard storage capacity.Key words: storage capacity, radiographic images, simcard